Launch of Guyana's Low Carbon Development Strategy - Jagdeo, Bharrat ([Office of the President] [Georgetown]GY, 2009)
Sets out a pathway to a new economy which builds future prosperity that is low-deforestation, low-carbon and climate resilient, in other words an economy that can address the three elements of the climate challenge in Guyana.